An influence of accelerated ageing on distinctness of image for coated offset prints - Tomić, Ivana; Karlović, Igor; Jurič, Ivana; Szentgyörgyvölgyi, Rozália (Univerzita Pardubice, 2013)
The accelerated ageing is a test method used to simulate the long term effects of heat, oxygen, sunlight, moist etc. over the short period of time. The influences of external parameters are mimicked within the environmental chambers by strictly defined, standard test conditions. Printed products are, as any other material, very susceptible to ageing. This is even more emphasized if they are exposed outdoor. In order to prevent mechanical and chemical damages, products are usually varnished or laminated. In this paper we investigated the influence of accelerated ageing of offset papers coated with different types of coating, with regard to distinctness of image. Since the distinctness of image describes the deviation of the spread of the light reflected at the specular angle, it is a better indicator of a product surface quality than specular gloss. As a samples for this study we used papers printed with conventional and hybrid inks and coated with aqueous and UV coatings. Distinctness of image was assessed for primary process colours before and after ageing, where ageing is performed in accordance to ISO 12040-1997 and ISO 4892-2:2006. From the obtained results it was concluded that the accelerated ageing leads to the increase of surface roughness of coated papers and hence to the decrease of distinctness of image. The same trend is found for each of the primary process colours.
Keywords: accelerated ageing; distinctness of image; coating